Transplant surgical templates for dental autotransplantation: a technical note - Tavennec Louise; Chataigner Pierre-Alexandre; Sorel Olivier; Fau Victor (EDP Sciences, 2019)
Introduction: This technical note presents the autotransplantation of an impacted third molar to replace a severely damaged homolateral molar using a surgical template of the tooth to be transplanted to prepare the recipient site based on an original protocol. Technique: Mandibular molar extraction is first performed, and autotransplantation is done after 7 days. Alveolar adjustment of the receiving socket is done using a resin replica of the tooth to be transplanted; the replica is obtained using DICOM diagnosis data. The three-dimensional (3D) replica is produced using 3D printing techniques with photopolymerizable methacrylate resin. Once the recipient site is ready, the transplant is avulsed. Immediate positioning of the tooth in the new socket will save a tremendous amount of extra-alveolar time. Cross-stitch sutures are done to obtain complete restraint, and endodontic treatment is administered after 15 days. Postoperative clinical and radiographic examination showed periodontal healing after postoperative 6 months. Comments: The use of the surgical template resulted in an extra-alveolar time of below 5 s and preservation of healthy periodontal ligament cells of the donor tooth as much as possible. Conclusion: The 3D technology, from imaging to printing, can drive the improvement of prognosis in a tooth autotransplantation protocol.